Bimbingan Agama pada Anak-Anak (Teladan QS: Luqman 12-19) - ., Syarifuddin (Alhadharah: Jurnal Ilmu Dakwah, 2014)
In the Quran Sura Luqman verse 12-19 God illustrated on a religious guidance by Luqman to his son. Furthermore, this paper tries to comment on the contents of the Quran Surah Luqman verse 12-19. In relation to religuous guidance and counseling, Luqman provides counseling and guidance to their children, not just limited to the messages only. However Luqman gives an example of such advice or guidance and this is what we need to emulate